1998
DOI: 10.1016/s0895-7061(98)00027-2
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Plasma Endothelin and Growth Factor Levels, and of Left Ventricular Mass, After Chronic AT1-Receptor Blockade in Human Hypertension

Abstract: The stimulation of autocrine and paracrine factors such as basic fibroblast- (bFGF) and platelet-derived (PDGF) growth factors mediates many of the growth-promoting actions of angiotensin II. The aim of this study was to evaluate the effect of chronic AT1-receptor blockade on plasma endothelin-1 (ET-1) and growth factors levels, and on left ventricular mass, in essential hypertension (EH). The study population consisted of 16 patients with mild-moderate EH, and 25 normotensive controls. In the EH patients unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…ET-1 is mainly released albuminally from the endothelium towards the underlying smooth muscle, and it is rapidly cleared from the circulation. In arterial hypertension high-to-low circulating values of ET-1 have been reported, 15,29,30 probably due to different methods of assay and different normal range, wideness of the population studied as well as different criteria of enrolment employed. Therefore, it is clear that there are a few difficulties in interpreting the significance of plasma ET-1 concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ET-1 is mainly released albuminally from the endothelium towards the underlying smooth muscle, and it is rapidly cleared from the circulation. In arterial hypertension high-to-low circulating values of ET-1 have been reported, 15,29,30 probably due to different methods of assay and different normal range, wideness of the population studied as well as different criteria of enrolment employed. Therefore, it is clear that there are a few difficulties in interpreting the significance of plasma ET-1 concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Nonetheless, data regarding plasma values of ET-1 in hypertensive subjects with both essential hypertension and renal parenchymal diseases, are still conflicting. [13][14][15] It has also been suggested that a potential increase in the expression of pre-pro-endothelin 1 constitutes one of the mechanisms implicated in TNF␣ glomerular haemodynamic effect. 16 The potential implication of TNF␣ in decreasing glomerular blood flow and filtration rate is explained by alterations in the balance between vasoconstrictive and vasodilating mediators.…”
Section: Introductionmentioning
confidence: 99%
“…The growth-promoting action of Ang II is largely mediated by autocrine and paracrine factors such as platelet-derived growth factor (PDGF) and basic fibroblast growth factor (bFGF). 62 ACE inhibition abolishes medial smooth muscle PDGF-AB biosynthesis and attenuates cell proliferation in injured carotid arteries. 63 In the rat carotid artery and in certain mesenteric microvessels, the mitogenic effects of Ang II are mediated by bFGF.…”
Section: Dtgr As a Model Of Hypertension And Ang Ii-related Effectsmentioning
confidence: 99%
“…23 In patients with hypertension or heart failure, chronic blockade of AT 1 resulted in a significant decrease in the circulating levels of TNF-␣. 24,25 More importantly, blockade of TNF-␣ by etanercept has been shown to prevent renal damage in genetically hypertensive rats and to lower blood pressure in rats with hypertension induced by Ang II and salt, suggesting a role for TNF-␣ in blood pressure regulation and renal injury. 26,27 A recent study showed that mice treated with etanercept prevented the hypertension and blunted the increase in superoxide production in response to Ang II.…”
mentioning
confidence: 99%